ANALISIS STRATEGI PEMASARAN BERBAGAI PRODUK BERBASIS IKAN BANDENG DI PROVINSI LAMPUNG - Deli, Rizky Okta; Widjaya, Sudarma; Endaryanto, Teguh (Jurnal Ilmu-Ilmu Agribisnis, 2018)
This research aimed to analyse marketing efficiency and marketing strategy of milkfish processing business in Lampung Province. The research was conducted in three milkfish processing businesses in February 2017. The marketing agencies which involved in product marketing are chosen by using snowball method. Data are analyzed using a qualitative and quantitative descriptive analysis. The results proved that the marketing system of milkfish processing business in Lampung Province has two cannels.  In the first channel producers sell their products directly to consumers, and in the second channel producers sell their products to consumers through merchants.  Marketing system is not efficient. The marketing strategy of milkfish processing business in Lampung Province in UD Sabily is increasing the use of technology in production process to create more varying and qualified products. ‘Jeng Sri’ creates more varying and qualified products to optimize high business competitiveness. ‘Sedap Lestari’ produces products according to consumers’ demand and utilized the low level of competition in the business environment for market control.Key words: marketing strategy, milkfish, SWOT analysis